Intrinsically Stretchable Organic Electrochemical Transistors with Rigid‐Device‐Benchmarkable Performance. Issue 29 (29th July 2022) - Liu, Dingyao; Tian, Xinyu; Bai, Jing; Wang, Yan; Cheng, Yixun; Ning, Weijie; Chan, Paddy K. L.; Wu, Kai; Sun, Junqi; Zhang, Shiming
Abstract: Intrinsically stretchable organic electrochemical transistors (OECTs) are being pursued as the next‐generation tissue‐like bioelectronic technologies to improve the interfacing with the soft human body. However, the performance of current intrinsically stretchable OECTs is far inferior to their rigid counterparts. In this work, for the first time, the authors report intrinsically stretchable OECTs with overall performance benchmarkable to conventional rigid devices. In particular, oxygen level in the stretchable substrate is revealed to have a significant impact on the on/off ratio. By employing stretchable substrates with low oxygen permeabilities, the on/off ratio is elevated from ≈10 to a record‐high value of ≈10 4, which is on par with a rigid OECT. The device remained functional after cyclic stretching tests. This work demonstrates that intrinsically stretchable OECTs have the potential to serve as a new building block for emerging soft bioelectronic applications such as electronic skin, soft implantables, and soft neuromorphic computing. Abstract : It is observed that the poor electrical performance of stretchable organic electrochemical transistors (OECTs) can be significantly improved by controlling the oxygen permeability of the elastic substrate. The overall performance of the optimized device is verified benchmarkable to a conventional rigid OECT.